A tessellation model for crack patterns on surfaces - Nagel, Werner (Image analysis and stereology, 2008)
This paper presents a model of random tessellations that reflect several features of crack pattern. There are already several theoretical results derivedwhich indicate that thismodel can be an appropriate referencemodel. Some potential applications are presented in a tentative statistical study.
Keywords: Image Processing, Computer-Assisted; Materiali, testiranje; Materials Testing; Raztezanje, trdnost; Slika, obdelava z računalnikom; Ceramics; ceramic; Keramika; Soil; Tensile Strength; Zemlja; Zemlya; razpoke; matematični modeli